Vibrational dynamical and thermodynamical characteristics of the superlattices based on the metal-hydrogen system - Feodosyev, S.B.; Gospodarev, I.A.; Grishaev, V.I.; Syrkin, E.S. (Физика низких температур, 2003)
The phonon spectra and vibrational thermodynamical characteristics of the Pd-H superlattices are investigated. Results of our calculations give a possibility to agree the data of neutronographic and calorimetric experiments and explain for the such systems the atomic mean square amplitudes and correlations between ones.